2010
DOI: 10.1007/s11280-010-0091-3
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Accessible Web Applications. An Aspect-Oriented Approach

Abstract: The development of accessible Web software is complicated for several reasons. Though some of them are technological, the majority are related with the need to compose different and, many times, unrelated design concerns which may be functional as in the case of most of the specific application's requirements, or non-functional such as Accessibility itself. In this paper, we present a novel approach to conceive, design and develop Accessible Web applications in an aspect-oriented manner. In order to reach our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 22 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…This is possible because aspects, as we have already explained, could be developed once and be reused in different Web projects. We refer the reader to [11] for a complete case study and evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…This is possible because aspects, as we have already explained, could be developed once and be reused in different Web projects. We refer the reader to [11] for a complete case study and evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Web-oriented software presents a certain degree of difficulty for its design and development, due to the characteristics that must cover the duration of the life cycle. One of the main complexities is the accessibility of applications, which is due to the development of both the team and the system [3]. According to Torrecilla, Sedeño, Escalona & Mejías, the different development methodologies in web engineering "concentrate essentially on the development phases and do not cover other areas, such as project estimation; quality assurance or team management" [4].…”
Section: Web-oriented Software Development Methodologiesmentioning
confidence: 99%
“…Although some authors provide instructions for the use of these guidelines [24] or propose simple frameworks in an attempt to maximize the benefits gained from the implementation of these guidelines [25], very few address the question of how to incorporate accessibility requirements in the software development process [26]. Where this does occur, individual suggestions are generally offered as opposed to comprehensive solutions [27].…”
Section: Related Workmentioning
confidence: 99%
“…Nevertheless, very few articles have been found that directly address the question of how to model accessibility according to WCAG, one of which has an aspect-oriented approach [26]. Thus, none of the previous approaches fully satisfy the accessibility standards.…”
Section: Related Workmentioning
confidence: 99%